Матеріали до словника вітчизняних мистців, ремісників, керівників художніх робіт та меценатів XVIII – початку XX ст. (за документами архіву Києво-Печерської лаври) - Уманцев, Ф. (Студії мистецтвознавчі, 2008)
The dictionary is created on the base of Kyiv Pechersk Lavra archive documents (KPL) which are kept now in the State historical archive of Ukraine. Materials dealing with names which activities are linked with Kyiv Pechersk monastery were collected in the research department of the Ukrainian Academy of Architecture while the author was working on his monograph “Gate Trinity Church of Kyiv Pechersk Lavra” published in 1970. The presented dictionary can be considered as a supplement to the dictionary of Ukrainian artists of the 16–18 centuries complied by precedent researches (Joltkovsky P. Art’s Life in Ukraine in the 16– 18 centuries. – K., 1983. – P. 109–178; Petrenko M. Ukrainian Gold 16–18 centuries. – K., 1983. – P. 146–197).